2011
DOI: 10.1121/1.3523340
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of distortion-product otoacoustic emission growth rates and slopes of forward-masked psychometric functions

Abstract: Slopes of forward-masked psychometric functions (FM PFs) were compared with distortion-product otoacoustic emission (DPOAE) input/output (I/O) parameters at 1 and 6 kHz to test the hypothesis that these measures provide similar estimates of cochlear compression. Implicit in this hypothesis is the assumption that both DPOAE I/O and FM PF slopes are functionally related to basilar-membrane (BM) response growth. FM PF-slope decreased with signal level, but this effect was reduced or reversed with increasing heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(110 reference statements)
0
2
1
Order By: Relevance
“…They confirmed the results of their earlier study, indicating that DPOAE and TMC-based estimates of compression were most similar at 4 kHz. In contrast to previous studies, Rodríguez et al (2011) compared the slopes of forward masked psychometric functions with DPOAE I/O function parameters at 1 and 6 kHz and found that these estimates of BM compression correlated only weakly at these frequencies. Investigation of the relationship between behavioral estimates of BM compression and hearing thresholds for tones has been provided by two studies conducted in normal-hearing adults (Dubno et al, 2007;Horwitz et al, 2007).…”
contrasting
confidence: 75%
“…They confirmed the results of their earlier study, indicating that DPOAE and TMC-based estimates of compression were most similar at 4 kHz. In contrast to previous studies, Rodríguez et al (2011) compared the slopes of forward masked psychometric functions with DPOAE I/O function parameters at 1 and 6 kHz and found that these estimates of BM compression correlated only weakly at these frequencies. Investigation of the relationship between behavioral estimates of BM compression and hearing thresholds for tones has been provided by two studies conducted in normal-hearing adults (Dubno et al, 2007;Horwitz et al, 2007).…”
contrasting
confidence: 75%
“…The lack of correspondence between different methods proposed to estimate cochlear compression is not new. One study showed that cochlear compression estimates using DPOAEs were not correlated with behavioural compression estimates in the same individual listeners 97 . Another study showed a correlation only at but not at lower frequencies 82 , and the correlation did not become stronger when efforts were made to reduce the DPOAE variability 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Distortion-product otoacoustic emissions (DPOAEs) are assumed to reflect the physiological nonlinear cochlear process in humans with normal outer hair cell function (Dorn et al 2001;Neely et al 2009). Moreover, input-output functions derived from DPOAEs and psychophysical measures provide generally similar estimates of basilar-membrane response growth, given that both are characterized by a nearly linear segment for low levels and a compressive segment for moderate levels (e.g., Dorn et al 2001;Williams and Bacon 2005 (Poling et al 2011;Rodriguez et al 2011). In this experiment, DPOAEs and DPOAE input-output functions were measured to provide estimates of basilarmembrane nonlinearities for each subject, to compare and correlate with level-dependent changes observed in recognition of vocoded speech.…”
Section: Introductionmentioning
confidence: 97%